2020
DOI: 10.1038/s41467-020-16143-6
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane damage causes NLRP3 activation and pyroptosis during Mycobacterium tuberculosis infection

Abstract: Mycobacterium tuberculosis is a global health problem in part as a result of extensive cytotoxicity caused by the infection. Here, we show how M. tuberculosis causes caspase-1/NLRP3/gasdermin D-mediated pyroptosis of human monocytes and macrophages. A type VII secretion system (ESX-1) mediated, contact-induced plasma membrane damage response occurs during phagocytosis of bacteria. Alternatively, this can occur from the cytosolic side of the plasma membrane after phagosomal rupture in infected macrophages. This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
185
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(197 citation statements)
references
References 106 publications
8
185
0
4
Order By: Relevance
“…Live intracellular Mycobacterium tuberculosis infection induced NLRP3-dependent IL-1β secretion and pyroptosis in human monocytes and macrophages ( 57 , 58 ). M. tuberculosis was shown to damage host cell plasma membrane either during phagocytosis or following phagocytosis and phagosome rupture from cytosolic side.…”
Section: The Nlrp3 Inflammasomementioning
confidence: 99%
See 1 more Smart Citation
“…Live intracellular Mycobacterium tuberculosis infection induced NLRP3-dependent IL-1β secretion and pyroptosis in human monocytes and macrophages ( 57 , 58 ). M. tuberculosis was shown to damage host cell plasma membrane either during phagocytosis or following phagocytosis and phagosome rupture from cytosolic side.…”
Section: The Nlrp3 Inflammasomementioning
confidence: 99%
“…M. tuberculosis was shown to damage host cell plasma membrane either during phagocytosis or following phagocytosis and phagosome rupture from cytosolic side. The damage caused by M. tuberculosis made plasma membrane permeable to both K + and Ca 2+ ions, which results in the NLRP3 inflammasome activation ( 58 ). M. tuberculosis was also shown to induce NLRP3-dependent pyroptosis in human monocytes which enables bacteria to spread immediately after cell death ( 58 ) However, a different study reported the NLRP3-dependent necrotic cell death that is independent of caspase-1 in primary human macrophages and THP-1 monocytes ( 59 ).…”
Section: The Nlrp3 Inflammasomementioning
confidence: 99%
“…Interestingly, once efferocytosis is blocked, cells undergo secondary necrosis, which promotes M. tuberculosis dissemination. Conversely, a recent publication showed that phagocytosis of trapped M. tuberculosis in pyroptotic cells triggers inflammasome activation and cell death in the new host cell that promote local spread of infection 118 . Neutrophilic efferocytosis of infected macrophages is also beneficial for the host upon Mycobacterium marinum infection in a zebrafish model, 119 but efferocytosis does not always need to involve professional phagocytes.…”
Section: Effector Mechanisms Of Cell Deathmentioning
confidence: 99%
“…Similarly, through pyroptosis macrophage infected with Mtb can destroy the survival environment of Mtb, and eventually prevent Mtb replication [19,20]. Mtb activated the canonical NLRP3 in ammasome by inducing potassium e ux upon infection of monocytes and macrophages, followed by GSDMD-dependent pyroptosis [21]. NLRP3 and AIM2 are considered two crucial kinds of pattern recognition receptors (PRR) which can activate cell pyroptosis after recognizing pathogen-associated molecular patterns (PAMP) [22,23].…”
Section: Discussionmentioning
confidence: 99%